Microtus arvalis - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus arvalis (Pallas, 1778). Nova Spec. Quadr. Glir. Ord., p. 78. TYPE LOCALITY: Germany; neotype from Leningrad Oblast. DISTRIBUTION: From C and N Spain throughout Europe (including Denmark) to western margin of Black Sea in the south and northeast to Kirov region (west of the Urals) in Russia; also populations on the Orkney Islands, Guernsey (Channel Islands), and Yeu (France) (see Niethammer and Krapp, 1982b, and Zagorodnyuk, 1991a). SYNONYMS: albus, arvensis, angularis, assimilis, asturianus, brauneri, calypsus, caucasicus, cimbricus, contigua, cunicularius, depressa, duplicatus, flava, fulva, galliardi, grandis, heptneri, howelkae, igmanensis, incertus, incognitus, levis, meldensis, meridianus, orcadensis, oyaensis, principalis, ronaldshaiensis, rousiensis, rufescentefuscus, ruthenus, sandayensis, sarnius, simplex, terrestris (of Schrank, 1798, not Linnaeus, 1758), variabilis, vulgaris, westrae. COMMENTS: Subgenus Microtus, arvalis species group sensu Zagorodnyuk (1990). Taxonomy and distribution generally reviewed by Corbet (1978c) and European populations by Niethammer and Krapp (1982). Morphological variation among samples from NE Spain was documented by Gosalbez and Sans-Coma (1977). Chromosomal data and comparisons with other species summarized by Zima and Krâl (1984a) and Burgos et al. (1989). Some of the synonyms listed and much of the southern and eastern distribution outlined for M. arvalis by Corbet (1978c) actually refer to either M. obscurus or M. rossiaemeridionalis (see those accounts). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on pages 518-519, DOI: 10.5281/zenodo.7353098